Frontispiece: Inherently Chiral Calixarenes: Synthesis and Applications. Issue 8 (6th February 2018) - Arnott, Gareth E.
Abstract : The chemistry surrounding the concept of inherently chiral calixarenes (ICCs), whose synthesis and application have only recently being realised, is covered in this article. One challenge in the area of ICC chemistry is the sheer breadth and scope for installing different aspects of inherent chirality. This article gives an overview of the main themes that have emerged in this area, including the more recent additions to the literature and the reports covering the applications of ICCs in asymmetric processes. For more details, see the Concept article by G. E. Arnott onpage 1744 ff.